2017
DOI: 10.1002/ca.22840
|View full text |Cite
|
Sign up to set email alerts
|

Central control of micturition in women: Brain‐bladder pathways in continence and urgency urinary incontinence

Abstract: Urinary incontinence disproportionately affects women. Anatomical textbooks typically describe continence mechanisms in women in the context of the pelvic floor support of the urinary bladder and the urethral sphincters. However, the urinary bladder and urethral sphincters are under the central control of the brain through a complex network of neurons that allow storage of urine followed by voiding when socially appropriate. Recent studies suggest that the most common type of urinary incontinence in women, urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…The thalamus is a complex of nuclei surrounded by the cerebral hemispheres and has an important role in both sensory and motor pathways for integrating somatosensory information (Herrero et al, ). As a part of the attention and awareness networks, thalamic activation during storage determines which afferent signals from the bladder should reach the cerebral cortex (Arya and Weissbart, ). During voiding, thalamic activation may represent the central role of the thalamus in co‐ordinating the integration of the decision to void generated in the PFC with the relaxation of the pelvic floor including the external urethral sphincter muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is a complex of nuclei surrounded by the cerebral hemispheres and has an important role in both sensory and motor pathways for integrating somatosensory information (Herrero et al, ). As a part of the attention and awareness networks, thalamic activation during storage determines which afferent signals from the bladder should reach the cerebral cortex (Arya and Weissbart, ). During voiding, thalamic activation may represent the central role of the thalamus in co‐ordinating the integration of the decision to void generated in the PFC with the relaxation of the pelvic floor including the external urethral sphincter muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable latrine use would require that cattle, like other species, learn to control a range of voluntary and reflex responses associated with toileting [ 9 , 10 , 11 ]. These include the ability to suppress impending voiding, a reflexive-like behaviour [ 9 , 11 ], then move to the latrine, a voluntary behaviour [ 12 , 13 ], and finally reinitiate voiding at the latrine.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable latrine use would require that cattle, like other species, learn to control a range of voluntary and reflex responses associated with toileting [ 9 , 10 , 11 ]. These include the ability to suppress impending voiding, a reflexive-like behaviour [ 9 , 11 ], then move to the latrine, a voluntary behaviour [ 12 , 13 ], and finally reinitiate voiding at the latrine. Dirksen et al [ 14 ] reviewed the literature on the toilet training of humans and other animals and reported that cattle have the neurophysiological and cognitive capabilities for toilet training, concluding that toilet training of cattle should be possible by using operant training methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through clinical correlations between both symptoms and lesions of the spine, along with early manipulative investigations, historical researchers were able to identify the spinal cord as an important conduit for signals to and from the brain. Contemporary researchers [2,[11][12][13][14][15][16][17] have used investigative techniques that have gone beyond surgical manipulation and stimulation to visualize the various components of the central Fig. 1 and cover figure Collage demonstrating physicians who have studied the spinal cord over human history.…”
Section: Resultsmentioning
confidence: 99%